The Influence of Spiritual Intelligence,Leadership, and Organizational Culture on Organizational Citizenship Behavior: A Study To Islamic Bank in Makassar City - Muhdar HM; St. Rahma (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
The aims of this study are to find out and to analys: (1) the influence of spiritual intelligence on organizational citizenship behavior; (2) the influence of leadership on organizational citizenship behavior; (3) the influence of organizationan culture on organizational citizenship behaviorThe population included all employees of Islamic Bank in Makassar City. There were 178 samples determined by using Slovin formula. The samples were selected in two stages: proportional and purposive sampling. The data were analyzed by using path analysis with the AMOS 21 program. The results show that: spiritual intelligence has a positive and significant influence on organizational citizenship behavior; leadership has a positive and significant influence on organizational citizenship behavior; organizational culture has a positive and significant influence on organizational citizenship behavior.